Paraoxonase 1 Polymorphisms in Patients With Primary Glomerulonephritis A Single-center Study in Turkey - (:unkn) unknown (IRANIAN SOC NEPHROLGY, 2012)
Introduction. Human paraoxonase 1 (PON1) is an enzyme related with high-density lipoprotein cholesterol. The link between genetic polymorphisms of PON1 and hyperlipidemia and increased lipid oxidation may explain these complications in the course of glomerular diseases. In this study, we aimed to investigate PON1 192 and PON1 55 polymorphisms in patients with primary glomerulonephritis and healthy individuals. Materials and Methods. Eighty-six patients with biopsy-proven primary glomerulonephritis and 50 healthy controls were included in the study. Clinical characteristics, lipid profile, paraoxonase activity, and PON1 genotypes (PON1 192 and PON1 55) of all of the participants were studied. Results. Histopathological diagnoses of the patients were membranoproliferative glomerulonephritis (53.5%), focal segmental glomerulosclerosis (33.7%), and membranous nephropathy (12.8%). The patients had lower PON1 activity levels than the healthy controls. No differences were observed in PON1 192 genotypes between the two groups. However, the controls were more likely to carry PON1 55 LM genotype (odds ratio, 4.10; 95% confidence interval, 1.96 to 8.61; P <.001) and M allele (odds ratio, 3.0; 95% confidence interval, 1.45 to 6.19; P =.003) compared to the patients with primary glomerulonephritis. There was a marked elevation in the frequency of PON1 55 LL genotype in the patients compared to the controls (odds ratio, 0.33; 95% confidence interval, 0.16 to 0.68; P =.003). Conclusions. This preliminary study shows that the LL genotype might be a risk factor for the development of primary glomerulonephritis and the M allele might be a protective factor against its progression.
Keywords: human PON1 protein; genetic polymorphism; glomerulonephritis; hyperlipidemias; HIGH-DENSITY-LIPOPROTEIN; NEPHROTIC SYNDROME; MOLECULAR-BASIS; SERUM; GLOMERULOSCLEROSIS; CELLS; RISK; DNA